Innovative utilization of the Moodle in postgraduate ODL courses at Universiti Sains Islam Malaysia - Zainuddin N.; Idrus R.; Mohd Jamal A.F. (Academic Conferences Limited, 2024)
Indexed by WOS/ Scopus